Існування низькоамплітудних подвійних шарів малої амплітуди у неізотермічній плазмі з двома температурами - Chattopadhyay, S. (Publishing house "Academperiodika", 2024)
In the presence of warm negative ions, ion-acoustic small-amplitude monotonic double layers are theoretically investigated in a plasma consisting of warm positive ions, warm positrons, and two-temperature non-isothermal electrons under the variation of the trapping parameters of electrons, concentration of positrons, and mass ratios of heavier negative ions to lighter positive ions by the Sagdeev pseudopotential method. The corresponding double layer solutions are also discussed for the same variation. Consequently, ion-acoustic solitary waves and double layers have been observed in auroral and magnetospheric plasmas with two-temperature electron distributions found in a laboratory, as well as in the space. This paper shows the effects of trapping parameters of electrons, positron concentration, and mass ratios of heavier negative ions to lighter positive ions on the Sagdeev potential function ψ(φ) and double layer solutions φDL for small-amplitude monotonic double layers. The results are presented graphically in Figs. 1 to 6.